Arsenic Transport in Rice and Biological Solutions to Reduce Arsenic Risk from Rice - Chen, Yanshan; Han, Yong-He; Cao, Yue; Zhu, Yong-Guan; Rathinasabapathi, Bala; Ma, Lena Q. (Frontiers in Plant Science, 2017)
Rice (Oryza sativa L.) feeds ∼3 billion people. Due to the wide occurrence of arsenic (As) pollution in paddy soils and its efficient plant uptake, As in rice grains presents health risks. Genetic manipulation may offer an effective approach to reduce As accumulation in rice grains. The genetics of As uptake and metabolism have been elucidated and target genes have been identified for genetic engineering to reduce As accumulation in grains. Key processes controlling As in grains include As uptake, arsenite (AsIII) efflux, arsenate (AsV) reduction and AsIII sequestration, and As methylation and volatilization. Recent advances, including characterization of AsV uptake transporter OsPT8, AsV reductase OsHAC1;1 and OsHAC1;2, rice glutaredoxins, and rice ABC transporter OsABCC1, make many possibilities to develop low-arsenic rice.